Knowledge-Based System ADNEXPERT to Assist the Sonographic Diagnosis of Adnexal Tumors - Brüning, J.; Becker, R.; Entezami, M.; Loy, Y.; Vonk, R.; Weitzel, H.; Tolxdorff, Th. (Methods of Information in Medicine, 1997)
ADNEXPERT is a knowledge-based system for the computer- assisted ultrasound diagnosis of adnexal tumors. In a case-based approach, ADNEXPERT used histopathologic and sonographic data from 2,290 adnexal tumors. After an ultrasound examination, the gynecologist interacts with the system. A maximum of 15 questions are posed; all but one question (age) relate to the sonographic findings. The help system gives online access to an ultrasound image library. Once the dialogue is complete, ADNEXPERT assesses the adnexal tumor pathology and makes a histological classification. A certainty factor (CF) model is used for knowledge representation. The CFs of the knowledge base are computed from the case database. During system evaluation, the accuracy of ADNEXPERT was tested by 69 new adnexal tumor cases, for which verified histopathological diagnoses were available. ADNEXPERT accurately assessed pathology in 49 cases (71%); in 10 cases (14%) correct indications to pathology were given; no diagnostic hints were attained in 2 cases (3%); and 8 cases (12%) were falsely diagnosed. Based on the positive results of the evaluation, ADNEXPERT will be tested under clinical conditions.
Keywords: Expert Systems; Knowledge-based Systems; Certainty Factors; Adnexal Tumors; Ultrasound Images; Computer-assisted Diagnosis